Morphological Awareness and Reading Difficulties in Adolescent Spanish-Speaking Language Minority Learners and Their Classmates. (January 2014) - Kieffer, Michael J.
This study investigated the role of morphological awareness weaknesses in the reading difficulties encountered by Spanish-speaking language minority learners and their native English-speaking peers in sixth grade. One hundred and thirty-eight students (82 language minority learners; 56 native English speakers) were assessed on English measures of reading comprehension, silent word reading fluency, and derivational morphological awareness. Students with specific reading comprehension difficulties, specific word reading difficulties, and combined difficulties were identified using categorical cut-scores. Findings indicated that morphological awareness differentiated skilled readers from students with reading difficulties. Substantial proportions of students with reading difficulties (38%–63%, depending on reading difficulty subtype) demonstrated weaknesses in morphological awareness. Language minority learners with reading difficulties were particularly likely to demonstrate weaknesses in morphological awareness (55%–64%), compared to native English speakers with similar reading difficulties (13%–50%). Findings suggest the diagnostic potential of morphological awareness for adolescent learners with reading difficulties, especially those from language minority backgrounds.